(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In this paper, a data hiding method is presented that hide the data in the compression domain. The Block Truncation Coding (BTC) method is used for hiding the information. The key point of the proposed method is to first apply traditional Block Truncation Coding and later it applied using Improved Block Truncation Coding (IBTC). Experimental results show that IBTC can embed a large amount of data in the compressed file while maintaining satisfactory image quality.